The success of insulin pump therapy: importance of education of patients and health professionals - Carić, Bojana; Marin, Saša; Malinović-Pančić, Jelena; Malešević, Gabrijela; Mirnić, Duška (Frontiers in Clinical Diabetes and Healthcare, 2024)
The purpose of the study is to investigate the importance of education and re-education for the proper use of the insulin pump (IP) in order to maintain stable glycemic control over an extended period.MethodsThe study was designed as a cross-sectional retrospective study. A total of 168 patients participated in a five-day structured education program in a small group. Following the initial education, 42 patients who met the criteria for continuation of IP treatment continued to be monitored every six months (period I). After six years of follow-up (period II) data from 36 patients were taken and analyzed. The data from the IP were downloaded from the IP Paradigm 754 "VEO" (Medtronic Inc., Illinois, USA) on the personal computer via the CareLink Pro software (Medtronic, Inc., Illinois).ResultsThe number of patients using the bolus calculator (BC+) for at least 50% of all administered boluses remained high in both periods. However, BC+ patients statistically significantly increased their A1C value in period II. The average number of hypoglycemias was statistically significantly increased in the group of BC+ patients in period II compared to period I (p=0.009). The continuous glucose monitors (CGM) were used only in period II, so the number of hypoglycemias in period I were roughly estimated.ConclusionsThe long-term success of IP therapy primary depends on the proper use of the device, highlighting the importance of good education and regular re-education for both patients and health professionals. Advanced hybrid technology systems could be particularly in settings with poorly organized healthcare, where re-education is not routinely provided and diabetes control relies heavily on the patient engagement.